Розробка методики обґрунтування ринкової стратегії транспортно-експедиторської компанії - Гладковська, Валентина Валеріївна; Раскевич, Ігор Вікторович (НТУ "ХПІ", 2015)
У статті досліджується проблема забезпечення конкурентоспроможності вітчизняних транспортно-експедиторських компаній в умовах невизначеності зовнішнього середовища їх функціонування, яка викликає необхідність вдосконалення методів та розвитку стратегічного підходу до управління транспортно-експедиторською діяльністю. Недостатня теоретична проробка методичних аспектів стратегічного аналізу, націлених на специфіку експедиторської діяльності, визначили актуальну потребу в вивченні поставленої проблеми.

Up to dute freight forwarder activity is most the develop dinamically. The Ukrainian market of forwarder activity services is on the stage of forming, and, presently, poorly presented by domestic forwarder activity companies able to give the complete spectrum of transport-logistic services and successfully to compete with their foreign partners. The problem of providing of competitiveness of the domestik freight forwarder company in the conditions of vagueness of environment of their functioning causes the necessity of perfection of methods and development of the strategic meth-od a management by a freight forwarder activity. For a survival in the changeable world of organization must look over the aims and strategies, bring them over in accordance with the changes of environment and organizations. Development and revision of strategy are the real necessity at considera-ble changes in an environment, also as in aims, and politics of organizations. Insufficient theoretical working of the methodical aspects of strategic analysis, aimed at the account of specific of a freight forwarder activity, defined an actual requirement in the deep study of the tix problem.
Amendment methodology reasoning of market strategy a freight forwarder company
Keywords: транспортно-експедиторська діяльність; конкурентоспроможність; фактори впливу; цінова політика; freight Forwarder Company; market strategy; competitiveness; factor; qualification; price politics